Rational design of a water-soluble, lipid-compatible fluorescent probe for Cu(i) with sub-part-per-trillion sensitivity - Morgan, M. T. (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
Fluorescence probes represent an attractive solution for the detection of the biologically important Cu(i) cation; however, achieving a bright, high-contrast response has been a challenging goal. Concluding from previous studies on pyrazoline-based fluorescent Cu(i) probes, the maximum attainable fluorescence contrast and quantum yield were limited due to several non-radiative deactivation mechanisms, including ternary complex formation, excited state protonation, and colloidal aggregation in aqueous solution. Through knowledge-driven optimization of the ligand and fluorophore architectures, we overcame these limitations in the design of CTAP-3, a Cu(i)-selective fluorescent probe offering a 180-fold fluorescence enhancement, 41% quantum yield, and a limit of detection in the sub-part-per-trillion concentration range. In contrast to lipophilic Cu(i)-probes, CTAP-3 does not aggregate and interacts only weakly with lipid bilayers, thus maintaining a high contrast ratio even in the presence of liposomes.